Novel triptorelin acetate-loaded microspheres prepared by a liquid/oil/oil method with high encapsulation efficiency and low initial burst release - Chen, Liqing; Ahmed, Atef Mohammed Qasem; Deng, Yibin; Cao, Dingyun; Du, Huanhuan; Cui, Jinghao; Lee, Beom Jin; Cao, Qingri (Journal of Drug Delivery Science and Technology, 2019)
Low encapsulation efficiency (EE) and high initial burst release are key issues for the development of microspheres loading highly water-soluble peptide drugs. In this study, novel triptorelin acetate-loaded microspheres with high EE and low initial burst release were prepared by a liquid/oil/oil (L/O/O) phase separation method using poly(lactic-co-glycolic acid) (PLGA) as the sustained-release carrier. The formulation of the microspheres and the preparation process were optimized in terms of particle size, surface morphology, EE, and in vitro drug release. Importantly, PLGA concentration, solvent and non-solvent ratio, solidification solvent volume, and solidification speed were found to significantly affect the properties of the obtained microspheres. The optimal microspheres present 50–100 μm spherical-shaped particles with remarkably high drug loading and EE. The in vitro drug release of these microspheres exhibit a delayed-release manner, starting to release drug at the third week and displaying approximately 20% drug release at day 28. Fourier transform infrared spectroscopy and differential scanning calorimetry results show that triptorelin acetate slightly interacted with PLGA, indicating that the drug was successfully encapsulated into PLGA microspheres. The drug content in the microspheres had no significant change after the 12-month storage at 4 °C, suggesting their excellent long-term stability. In conclusion, novel triptorelin acetate-loaded PLGA microspheres have been achieved via the L/O/O phase separation method to effectively improve the EE and reduce the initial burst release.
Keywords: Initial burst release; Phase separation; Physicochemical characterization; PLGA microsphere; Triptorelin acetate